The Effect of My Q-Map Method on Improving Critical Thinking Abilities in Memorizing The Quran in the Tahfidz Program - Suci Hidayati; Indah Wigati; Nurlaila (Institut Agama Islam An-Nawawi Purworejo, 2025)
Memorizing the Qur'an is an obligation and one of the virtues for Muslims, but many students face difficulties in the memorization process, either due to lack of motivation or critical thinking skills that have not been properly honed. In the context of education, this challenge requires special attention to find effective solutions so that the process of memorizing the Qur'an can run more easily and enjoyably. Therefore, this study is important to explore how innovative methods, such as My Q-MAP, can play a role in increasing students' motivation and critical thinking skills. This study aims to analyze the effect of the My Q-MAP method on both aspects in the tahfidz program at SMP IT An-Nuriyah Sekayu. This study uses a quasi-experimental design with a pretest-posttest control group approach involving 40 students as samples. Data collection techniques are carried out through tests and questionnaires to measure students' critical thinking skills and motivation. The results of the study indicate that the My Q-MAP method has a significant effect on increasing students' motivation and critical thinking skills in memorizing the Qur'an. This research is expected to contribute as a reference in improving the effectiveness of teaching methods and student motivation in the tahfidz program. In conclusion, the application of the My Q-MAP method can improve both aspects, and further research is recommended to test the application of this method in a broader context.